2022
DOI: 10.1155/2022/1716008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Fatigue Resistance of Nickel–Titanium Rotary Instruments after Simulated Clinical Use

Abstract: Objective. Cyclic fatigue occurred in the curved canal when the instrument freely rotated leading to repeated compressive and tensile stresses. This study aims to evaluate the cyclic fatigue resistance (CFR) of new and used 2Shape and AF F-One rotary instrument systems by using an artificial stainless-steel canal. Methods. A total of 80 rotary nickel–titanium (NiTi) instruments of two systems were used, 2Shape/TS2 and AF F-ONE/F5 (40 in each group). The instruments were subdivided into group A 20 instruments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The time to fracture of flat‐side instruments was lower compared with the reciprocating ones, which can be attributed to the kinematics itself (under the “rotary vs reciprocating” comparison) and the observed irregularities on their surfaces (under the “clockwise vs counter‐clockwise oscillatory asymmetric motion with equivalent angles of rotation” comparison). Whilst previous studies have shown that the flat‐side design (Gambarini et al, 2019; Ubaed & Bakr, 2022) and the clockwise oscillatory asymmetric motion can increase the time to fracture of rotary instruments (Martins et al, 2020), this effect was not observed in the Platinum V.EU. On the other hand, the AF F One Blue showed an extension in time to fracture, which ultimately resulted in a significantly lower cyclic fatigue strength for the Platinum V.EU.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The time to fracture of flat‐side instruments was lower compared with the reciprocating ones, which can be attributed to the kinematics itself (under the “rotary vs reciprocating” comparison) and the observed irregularities on their surfaces (under the “clockwise vs counter‐clockwise oscillatory asymmetric motion with equivalent angles of rotation” comparison). Whilst previous studies have shown that the flat‐side design (Gambarini et al, 2019; Ubaed & Bakr, 2022) and the clockwise oscillatory asymmetric motion can increase the time to fracture of rotary instruments (Martins et al, 2020), this effect was not observed in the Platinum V.EU. On the other hand, the AF F One Blue showed an extension in time to fracture, which ultimately resulted in a significantly lower cyclic fatigue strength for the Platinum V.EU.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has compared the first launched AF F One single‐file NiTi rotary system (size 25, 0.06 taper; Fanta Dental Material Co.) that is made of a proprietary AF‐R wire technology to various rotary and reciprocating systems. These studies showed that AF F One instruments had lower cyclic fatigue resistance than 2Shape instrument after clinical usage (Ubaed & Bakr, 2022), produced more debris but better cleaning ability than One Shape and OneCurve systems (Mogahed et al, 2021), had better shaping ability than a prototype instrument in simulated canals (Di Nardo et al, 2020), were less effective than certain reciprocating systems in removing calcium silicate‐based sealer (Madarati et al, 2023) and in eliminating Enterococcus faecalis biofilm from infected root canals (Hamed et al, 2022), but showed improved resistance to flexural fatigue compared with a prototype instrument (Gambarini et al, 2019). These preliminary findings indicate that using flat design instruments instead of other market‐available options may not offer the advantages claimed by manufacturers, and further research is necessary to assess their mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have reported conflicting results regarding the performance of flat-side instruments. For instance, Ubaed and Bakr (2022) found that AF F-One exhibited lower cyclic fatigue resistance compared to 2Shape instruments after clinical usage, whilst Mogahed et al (2021) observed that AF F-One generated more debris but demonstrated superior cleaning ability compared to One Shape and OneCurve systems. Conversely, Di Nardo et al (2020) reported better shaping ability of flat-side instruments, and Gambarini et al (2019) demonstrated improved resistance to flexural fatigue in comparison to nonflat-side prototype counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The sudden fracture of instruments inside the root canal is a major concern in clinical practice and this complication can compromise the entire endodontic treatment [4]. Considering that cyclic fatigue is the most common cause of instrument fracture, it has become a frequent topic of study among endodontic practitioners [5,6]. It can be said with certainty that almost no metal or alloy has introduced as many revolutionary new therapeutic possibilities in dental medicine and endodontics as the NiTi alloy [7].…”
Section: Introductionmentioning
confidence: 99%